SnoRNAs from the filamentous fungus Neurospora crassa: structural, functional and evolutionary insights - Liu, Na (BioMed Central, 2009)
BACKGROUND: SnoRNAs represent an excellent model for studying the structural and functional evolution of small non-coding RNAs involved in the post-transcriptional modification machinery for rRNAs and snRNAs in eukaryotic cells. Identification of snoRNAs from Neurospora crassa, an important model organism playing key roles in the development of modern genetics, biochemistry and molecular biology will provide insights into the evolution of snoRNA genes in the fungus kingdom. RESULTS: Fifty five box C/D snoRNAs were identified and predicted to guide 71 2'-O-methylated sites including four sites on snRNAs and three sites on tRNAs. Additionally, twenty box H/ACA snoRNAs, which potentially guide 17 pseudouridylations on rRNAs, were also identified. Although not exhaustive, the study provides the first comprehensive list of two major families of snoRNAs from the filamentous fungus N. crassa. The independently transcribed strategy dominates in the expression of box H/ACA snoRNA genes, whereas most of the box C/D snoRNA genes are intron-encoded. This shows that different genomic organizations and expression modes have been adopted by the two major classes of snoRNA genes in N. crassa . Remarkably, five gene clusters represent an outstanding organization of box C/D snoRNA genes, which are well conserved among yeasts and multicellular fungi, implying their functional importance for the fungus cells. Interestingly, alternative splicing events were found in the expression of two polycistronic snoRNA gene hosts that resemble the UHG-like genes in mammals. Phylogenetic analysis further revealed that the extensive separation and recombination of two functional elements of snoRNA genes has occurred during fungus evolution. CONCLUSION: This is the first genome-wide analysis of the filamentous fungus N. crassa snoRNAs that aids in understanding the differences between unicellular fungi and multicellular fungi. As compared with two yeasts, a more complex pattern of methylation guided by box C/D snoRNAs in multicellular fungus than in unicellular yeasts was revealed, indicating the high diversity of post-transcriptional modification guided by snoRNAs in the fungus kingdom.